Genome-Wide Analysis of Alternative Splicing during Host-Virus Interactions in Chicken - Weiwei Liu; Yingjie Sun; Xusheng Qiu; Chunchun Meng; Cuiping Song; Lei Tan; Ying Liao; Xiufan Liu; Chan Ding (Viruses, 2021)
The chicken is a model animal for the study of evolution, immunity and development. In addition to their use as a model organism, chickens also represent an important agricultural product. Pathogen invasion has already been shown to modulate the expression of hundreds of genes, but the role of alternative splicing in avian virus infection remains unclear. We used RNA-seq data to analyze virus-induced changes in the alternative splicing of Gallus gallus, and found that a large number of alternative splicing events were induced by virus infection both in vivo and in vitro. Virus-responsive alternative splicing events preferentially occurred in genes involved in metabolism and transport. Many of the alternatively spliced transcripts were also expressed from genes with a function relating to splicing or immune response, suggesting a potential impact of virus infection on pre-mRNA splicing and immune gene regulation. Moreover, exon skipping was the most frequent AS event in chickens during virus infection. This is the first report describing a genome-wide analysis of alternative splicing in chicken and contributes to the genomic resources available for studying host–virus interaction in this species. Our analysis fills an important knowledge gap in understanding the extent of genome-wide alternative splicing dynamics occurring during avian virus infection and provides the impetus for the further exploration of AS in chicken defense signaling and homeostasis.